Evidence-Based Cosmetic Breast Surgery - Swanson, Eric.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Insisting on an evidence-based approach, Dr. Swanson brings the light of science to bear on the many controversies in cosmetic breast surgery today. Conventional wisdom is challenged with factual analysis, made possible by Dr. Swanson$1 (Bs large body of published research. In his hallmark detailed style, the author lays the foundation with clinical studies, measurements, and patient-reported outcomes. The work is all here in one place for the first time, leading to some surprising conclusions. For plastic surgeons who prefer data to dogma, Evidence-Based Cosmetic Breast Surgery provides a unique and invaluable resource.s
1. Evidence-Based Medicine -- 2. A Measurement System and Ideal Breast Shape -- 3. Breast Augmentation -- 4. Complications of Breast Augmentation -- 5. The Myth of Breast Autoaugmentation -- 6. Mastopexy and Breast Reduction -- 7. All-Seasons Vertical Augmentation Mastopexy -- 8. Breast Reduction Plus Implants -- 9. Gynecomastia Surgery.
Keywords: Medicine; Plastic surgery; Medicine & Public Health; Plastic surgery